+0  
 
0
135
1
avatar

Hallo kann mir hier jemand diese Gleichung nach S auflösen: y=R-1/2*sqrt(4*R^2-S^2)

 15.12.2020
 #1
avatar+2217 
+1

\(y=R-\frac{1}{2} \cdot \sqrt{4R^2-S^2} \ \ |-R \\ y-R -\frac{1}{2} \cdot \sqrt{4R^2-S^2} \ \ | \cdot(-2) \\ 2R-2y=\sqrt{4R^2-S^2} \ \ |^2 \\ (2R-2y)^2 = 4R^2-S^2 \\ 4R^2-8Ry+4y^2=4R^2-S^2 \ \ | -4R^2 \\ 4y^2-8Ry=-S^2 \ \ | \cdot(-1) \\ 8Ry-4y^2=S^2 \ \ | \sqrt. \\ \sqrt{8Ry-4y^2} =S\)

 

Freilich, ich hoff das ist verständlich so!

 15.12.2020

16 Benutzer online

avatar
avatar
avatar